2021
DOI: 10.1101/2021.03.19.21253975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mortality in individuals treated with COVID-19 convalescent plasma varies with the geographic provenance of donors

Abstract: Treatment and prevention of coronavirus disease 2019 (COVID-19) have attempted to harness the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) including the development of successful COVID-19 vaccines and therapeutics (e.g., Remdesivir, convalescent plasma [CP]). Evidence that SARS-CoV-2 exists as quasispecies evolving locally suggests that immunological differences may exist that could impact the effectiveness of antibody-based treatments and vaccines. Regional variants of SARS-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…There was also no Delta construct for the pseudovirus assay system. This study was limited to Canadian blood donors 20 . Specimens were also collected from routine blood donors and not qualified convalescent plasma donors in Canada 7 .…”
Section: Discussionmentioning
confidence: 99%
“…There was also no Delta construct for the pseudovirus assay system. This study was limited to Canadian blood donors 20 . Specimens were also collected from routine blood donors and not qualified convalescent plasma donors in Canada 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Convalescent plasma is also adaptable to changing conditions. As variant SARS-CoV-2 strains continue to emerge, convalescent plasma donated by survivors of infections with variant strains represents an immediately deployable therapeutic for patients identified with a variant infection, whereas other immune therapies may require (re)development to more specifically target new viral strains ( 16 19 ).…”
Section: Principles Of Convalescent Plasma Therapymentioning
confidence: 99%
“…Pooling these available survival data demonstrated a 11% relative improvement in 28-day survival associated with convalescent plasma compared to control (88 vs. 79%) ( Figure 2B ). While the effect of convalescent plasma on mortality was found to be statistically significant in only two RCTs ( 42 , 71 ), it is important to highlight that signals of efficacy have emerged despite several limitations, including trials that (i) were underpowered due to declining local infection rates and early termination ( 27 , 43 ), (ii) transfused convalescent plasma units with unknown or low anti-SARS-CoV-2 antibody levels ( 30 ), (iii) transfused severely ill patients that had progressed to severe COVID-19 ( 11 , 27 ), and (iv) used prepositioned plasma units, which may not have accounted for SARS-CoV-2 variants ( 18 , 19 ). Transfusion of low antibody titer plasma to patients with severe COVID-19 reduces the opportunity to achieve the survival benefit associated with convalescent plasma.…”
Section: Convalescent Plasma Therapy For Covid-19: Mosaic Of Clinical Evidencementioning
confidence: 99%
“…Given recent large, randomized studies that have not shown benefit in general hospitalized cohorts, it is important to put the positive result of our study in context. This study has several unique characteristics that may have contributed to the demonstrated benefit, including the early administration of two units of locally sourced, plasma in a highly comorbid, majority antibody seronegative population [29,30]. In addition, we employed a sensitive primary outcome measure enabling a composite characterization of clinical status [31].…”
Section: Discussionmentioning
confidence: 99%